Islamic Education in the Perspective of the International World Muslim Conference on Education Ontological, Epistemological, axiological examination - Amsal Qori Dalimunthe; Salminawati; Usiono; Neng Nurcahyati Sinulingga (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
At a time when the Western world was progressing, the Islamic world no longer dominated science and was even left behind with the arrival of Western secularism that dominated science with its modern style, so there was concern for Muslim thinkers. On this basis, a world conference on Islamic education was held. This paper aims to explain the study of ontology, epistemology, and axiology of Islamic education in the perspective of the World Islamic Education Conference. The method used in this writing is library research. The results of this study show that this international Islamic education seminar does not have a specific time, but can be held at any time according to the agreement. Second, the Islamic education curriculum is universal and covers a wide range of topics. Third, there is no scientific barrier that separates general science and religious science. Fourth, scientific integration is necessary. Fifth, curriculum integration for Islamic educational institutions today is certainly very important, especially in advancing Islamic education in today's digital era. Keywords: Islamic Education , Science, International Confrence